Implementation and staff understanding of shared decision-making in the context of recovery-oriented care across US Veterans Health Administration (VHA) inpatient mental healthcare units: a mixed-methods evaluation. Issue 5 (30th May 2022) - Eliacin, Johanne; Carter, Jessica; Bass, Emily; Flanagan, Mindy; Salyers, Michelle P; McGuire, Alan
Abstract : Objectives: To examine the understanding and practice of shared decision-making (SDM) within the context of recovery-oriented care across Veterans Health Administration (VHA) inpatient mental healthcare units. Design: VHA inpatient mental health units were scored on the Recovery-Oriented Acute Inpatient Scale (RAIN). Scores on the RAIN item for medication SDM were used to rank each site from lowest to highest. The top 7 and bottom 8 sites (n=15) were selected for additional analyses using a mixed-methods approach, involving qualitative interviews, observation notes and quantitative data. Setting: 34 VHA inpatient mental health units located in every geographical region of the USA. Participants: 55 treatment team members. Results: Our results identified an overarching theme of 'power-sharing' that describes participants' conceptualisation and practice of medication decision-making. Three levels of power sharing emerged from both interview and observational data: (1) No power sharing: patients are excluded from treatment decisions; (2) Limited power sharing: patients are informed of treatment decisions but have limited influence on the decision-making process; and (3) Shared-power: patients and providers work collaboratively and contribute to medication decisions. Comparing interview to observational data, only observational data indicating those themes differentiate top from bottom scoring sites on the RAIN SDM item scores. All but one top scoring sites indicated shared power medication decision processes, whereas bottom sites reflected mostly no power sharing. Additionally, our findings highlight three key factors that facilitate the implementation of SDM: inclusion of veteran in treatment teams, patient education and respect for patient autonomy. Conclusions: Implementation of SDM appears feasible in acute inpatient mental health units. Although most participants were well informed about SDM, that knowledge did not always translate into practice, which supports the need for ongoing implementation support for SDM. Additional contextual factors underscore the value of patients' self-determination as a guiding principle for SDM, highlighting the role of a supporting, empowering and autonomy-generating environment.